PENGARUH GERAKAN SENAM OTAK TERHADAP PERKEMBANGAN SOSIAL ANAK ADHD DI SEKOLAH BERKEBUTUHAN KHUSUS - Putu Susy Natha Astini (Jurnal Gema Keperawatan, 2018)
ADHD have damage to the frontal limbic system with the primary symptoms are not able to focus, hyperactivity and impulsivity. Brain Gym is a collection of simple movements that can help optimize the development of the child. This study  aims to determine the effect of Brain Gym Movement for Social Development of Children with ADHD at Special Needs School Denpasar City.  This research  was  Pre Experimental with the study design The One Group Pretest Posttest Design.This research had been done  from June to October 2015,  at the School with Special Needs  in SLBA and Youth Shine Academy. The Number of sample are 28 children  ADHD with  6-12 years  old, using total sampling. The data analysis using Paired t-test  with a significance level of alpha = 0.05, Sig. (2 Tailed) 0,0001, thats  means   P value 0.05 means There is a significant influence were given of Brain Gym movements Social Development in ADHD Children with Special Needs School. It is sugested the results obtained to be used as a reference that children with ADHD were given the Brain Gym movements on a regular  will help the social development of children with attention more better, controlled activity and can control impulses properly